Molecular Epidemiology of Enterovirus D68 from 2013 to 2014 in Philippines - Furuse, Yuki (J Clin Microbiol, 2015)
Enterovirus D68 (EV-D68) has been recognized as an important cause of acute respiratory infections. Here we report the molecular epidemiology of EV-D68 in Philippines from 2013 to 2014; we found cases in areas affected by Typhoon Haiyan and found new strains in the country.